World Englishes : a cognitive sociolinguistic approach - Wolf, Hans-Georg, 1963- (Applications of cognitive linguistics, 2009)
The book is the first of its kind to establish Cognitive Linguistics as a research paradigm within the field of world Englishes. The authors survey the main tenets of both areas of linguistic enquiry and suggest that the theoretical and methodological apparatus developed both within Cognitive Linguistics generally and within its novel sub-discipline Cognitive Sociolinguistics can overcome certain limitations inherent in traditional approaches to cultural variation in language. They present a case study of the linguistic realization of the cultural model of community in African English as an ex.